"These days will never be forgotten …": A critical mass approach to online activism. Issue 1 (January 2015) - Ghobadi, Shahla; Clegg, Stewart
Abstract Social activists increasingly wield the power of the Internet technology to penetrate organizational boundaries and enable social and political change. Yet, research on activism beyond organizational boundaries and the role that new technology may play in it is scarce. This study explores this phenomenon by studying the dynamics of social activism through the Internet for expressing resistance to a powerful organizational regime. We first develop a critical mass approach to online activism to understand longitudinal data (2009–2013) collected from three YouTube-based cases and supplementary interviews. We then integrate the results of within-case and cross-case analyses in a process model that explains how online activism started, generated societal outcomes, and changed over time. The model suggests that online activism helped organize collective actions and amplify the conditions for revolutionary movements to form. Yet, it provoked elites' reactions such as Internet filtering and surveillance, which do not only promote self-censorship and generate digital divide, but contribute to the ultimate decline of activism over time. We provide a theoretical path for studying the phenomenon of online activism and present opportunities for organizations and social activists to direct online activities' focus from one being based on the creation of 'knowers' to one based on the empowerment of 'learners'.